The relationship between tourist perception on hotel environmental management and tourist loyalty in Port Dickson, Negeri Sembilan - Fara Adilah, Firdaus Mohd Rom (2014)
This quantitative project paper entitled The Relationship Between Tourist Perception on Hotel Environmental Management (HEM) and Tourist Loyalty (TLOYALTY) in Port Dickson, Negeri Sembilan, aims to determine the tourist perception on hotel environmental management and their loyalty towards hotel that there are staying. The hotels involved are among three and four star hotels in Port Dickson, Negeri Sembilan. Respondents for this study comprised 384 of tourist from different background with majority of it comes from the government sector. Data were analyzed using SPSS version 22. Tests conducted were Pearson correlation and multiple regressions. The correlation between independent variable Sustainable Tourism Practices (STP) and TLOYALTY is 0.539 or 53.9% correlated and the significant value is pe0.01. They are highly correlated. The correlation between independent variable Health and Safety Environmenta (HSE) and TLOYALTY is 0.683 or 68.3% correlated and the significant value is pe0.01. They are correlated. The correlation between STP and HSE is 0.576 or 57.6% is high. The correlation between HEM and dependent variable TLOYALTY is 0.690 or 69% correlated and the significant value is pe0.01. They are highly correlated. The Pearson correlation showed that HEM was correlated with TLOYALTY. Regression analysis showed that 0.50 or 50% of the variance in tourist loyalty were explained by sustainable tourism practices and health and safety environment under the main independent variables that is hotel environmental management. Meanwhile the coefficients data showed that health and safety environment variables has higher impact (0.546) on the tourist loyalty compared to sustainable tourism practices (0.234) in terms of tourist perception. However, both variables have positive tourist perception and significant relationship with tourist loyalty. Recommendations were suggested that to incorporate other enabling factor such as hotel service innovation where it may influence the dynamic relationship between tourist perception and their loyalty on green tourism. Future studies should examine the tourist perception and their loyalty relationship based on different types of services or other service sector such as on the non-accommodation tourism operator perspective. Expanding this study with other region or countries which have different cultural background could provide more evidence of universal factors affecting the tourist perception and their loyalty towards hotel on green tourism.